New Interatheriines (Interatheriidae, Notoungulata) from the Paleogene of Central Chile and Southern Argentina - Hitz, Ralph B. (2000)
Two new interatheriines (Interatheriidae, Notoungulata), Santiagorothia chiliensis and Proargyrohyraxnew interatheriines (Interatheriidae, Notoungulata), Santiagorothia chiliensis and Proargyrohyrax curanderensis, are described from the transitional Eocene/Oligocene Tinguiriricaare described from the transitional Eocene/Oligocene Tinguiririca Fauna, central Chile, and from roughly coeval localities in Chubut and Rio Negro provinces, Argentina. The former occurs in both central Chile and Argentina, whereas the latter occurs only in Argentina. Several Argentine specimens are referred to Eopachyruchos, an interatheriine for which an emended diagnosis is presented. The taxonomic status of Argyrohyrax acuticostatuscentral Chile, and from roughly coeval localities in Chubut and Rio Negro provinces, Argentina. The former occurs in both central Chile and Argentina, whereas the latter occurs only in Argentina. Several Argentine specimens are referred to Eopachyruchos, an interatheriine for which an emended diagnosis is presented. The taxonomic status of Argyrohyrax acuticostatusThe former occurs in both central Chile and Argentina, whereas the latter occurs only in Argentina. Several Argentine specimens are referred to Eopachyruchos, an interatheriine for which an emended diagnosis is presented. The taxonomic status of Argyrohyrax acuticostatusin Argentina. Several Argentine specimens are referred to Eopachyruchos, an interatheriine for which an emended diagnosis is presented. The taxonomic status of Argyrohyrax acuticostatuswhich an emended diagnosis is presented. The taxonomic status of Argyrohyrax acuticostatus is discussed and an emended description is provided. Additionally, we propose a phylogeneticdiscussed and an emended description is provided. Additionally, we propose a phylogenetic taxonomic definition for the name Interatheriinae.definition for the name Interatheriinae. The transitional Eocene/Oligocene localities under consideration here occur within a poorlytransitional Eocene/Oligocene localities under consideration here occur within a poorly known interval of the South American Land Mammal Age (SALMA) sequence, intermediateinterval of the South American Land Mammal Age (SALMA) sequence, intermediate between the Mustersan and Deseadan SALMAs. This temporal interval spans a transition inthe Mustersan and Deseadan SALMAs. This temporal interval spans a transition in South American mammal evolution between older faunas dominated by various archaic, dentallyAmerican mammal evolution between older faunas dominated by various archaic, dentally conservative herbivores and younger faunas dominated by later diverging clades of moreherbivores and younger faunas dominated by later diverging clades of more hypsodont forms. The Tinguiririca Fauna, the age of which is bracketed radioisotopically, recordsforms. The Tinguiririca Fauna, the age of which is bracketed radioisotopically, records the first or last occurrence of seven subfamilial or higher level taxa. Although the Argentinefirst or last occurrence of seven subfamilial or higher level taxa. Although the Argentine localities are unconstrained geochronologically, similar faunal composition allows tentativeare unconstrained geochronologically, similar faunal composition allows tentative correlation to the Tinguiririca Fauna. Not unexpectedly, therefore, Santiagorothia chiliensisto the Tinguiririca Fauna. Not unexpectedly, therefore, Santiagorothia chiliensis and Proargyrohyrax curanderensis represent the earliest known interatheriines, a groupProargyrohyrax curanderensis represent the earliest known interatheriines, a group previously restricted to Deseadan SALMA (Late Oligocene/Early Miocene) and younger faunas.restricted to Deseadan SALMA (Late Oligocene/Early Miocene) and younger faunas. Santiagorothia chiliensis and Proargyrohyrax curanderensis are considered interatheriineschiliensis and Proargyrohyrax curanderensis are considered interatheriines based on their possession of the following diagnostic features of the clade thus named: deepon their possession of the following diagnostic features of the clade thus named: deep parastyle/paracone groove on P2-4; very shallow parastyle/paracone groove on upper molars;groove on P2-4; very shallow parastyle/paracone groove on upper molars; smooth posterior ectoloph on upper molars; very high-crowned cheek teeth; distinctly bilobedposterior ectoloph on upper molars; very high-crowned cheek teeth; distinctly bilobed p3-m3 with persistent labial and lingual sulci; auditory bulla lapping posteriorly onto the paraoccipital process; and maxilla excluded from the superior orbital border by a silver ofwith persistent labial and lingual sulci; auditory bulla lapping posteriorly onto the paraoccipital process; and maxilla excluded from the superior orbital border by a silver ofand maxilla excluded from the superior orbital border by a silver of anteriorly projecting frontal (although Proargyrohyrax curanderensis is known only from dentalprojecting frontal (although Proargyrohyrax curanderensis is known only from dental remains). Santiagorothia chiliensis and Proargyrohyrax curanderensis are most readily distinguishedSantiagorothia chiliensis and Proargyrohyrax curanderensis are most readily distinguished from other interatheriines in possessing cheek teeth with closed roots. Another distinctionother interatheriines in possessing cheek teeth with closed roots. Another distinction concerns the pattern of upper molar wear in Santiagorothia chiliensis and Proargyrohyraxthe pattern of upper molar wear in Santiagorothia chiliensis and Proargyrohyrax curanderensis: as wear proceeds, a lingual sulcus closes to form an isolated fossette,wear proceeds, a lingual sulcus closes to form an isolated fossette, whereas in other interatheriines this sulcus remains open.in other interatheriines this sulcus remains open.